The Impact of Islamization on the Padjajaran Kingdom: Educational Systems and Social Values in Sundanese Society - Usman Supendi; Syofiah Pribadi; Fitria Eka Dewi Murni (CV. Creative Tugu Pena, 2025)
This study aims to investigate the impact of Islamization on the Padjajaran Kingdom, particularly in relation to the transformation of educational systems and the evolution of social values within Sundanese society. Employing a qualitative approach and historical case study method, the research focuses on the West Java region, which was historically part of the Padjajaran Kingdom. The findings reveal that Islamization did not merely influence religious conversion but also brought about significant transformations in the educational landscape, with pesantren and madrasah emerging as centers of holistic learning. Furthermore, the social values of Sundanese society underwent notable changes, including the adoption of principles such as justice, tolerance, and brotherhood introduced through Islamic teachings. Although the Padjajaran Kingdom did not fully transform into an independent Islamic state, Islamic influences gradually permeated and shaped its cultural and social structures. This study contributes to the historiography of Islamization in Indonesia by highlighting its multifaceted impact beyond religious aspects, particularly in education and social transformation. It offers a nuanced understanding of how Islamic values were integrated into Sundanese society and provides new insights into the role of Islam in shaping regional identity and socio-cultural development in pre-modern West Java.